Cryptic Sulfur Incorporation in Thioangucycline Biosynthesis. (17th February 2021) - Cao, Mingming; Zheng, Chengjian; Yang, Dong; Kalkreuter, Edward; Adhikari, Ajeeth; Liu, Yu‐Chen; Rateb, Mostafa E.; Shen, Ben
Abstract: Sulfur incorporation into natural products is a critical area of biosynthetic studies. Recently, a subset of sulfur‐containing angucyclines has been discovered, and yet, the sulfur incorporation step is poorly understood. In this work, a series of thioether‐bridged angucyclines were discovered, and a cryptic epoxide Michael acceptor intermediate was revealed en route to thioangucyclines (TACs) A and B. However, systematic gene deletion of the biosynthetic gene cluster (BGC) by CRISPR/Cas9 could not identify any gene responsible for the conversion of the epoxide intermediate to TACs. Instead, a series of in vitro and in vivo experiments conclusively showed that the conversion is the result of two non‐enzymatic steps, possibly mediated by endogenous hydrogen sulfide. Therefore, the TACs are proposed to derive from a detoxification process. These results are expected to contribute to the study of both angucyclines and the utilization of inorganic sulfur in natural product biosynthesis. Abstract : The cryptic incorporation of inorganic sulfur into thioangucycline biosynthesis was confirmed to be non‐enzymatic by heterologous expression, systematic gene deletion, and in vitro experiments. A stable epoxide‐containing angucycline was identified as the final natural product and precursor to the thioether‐bridged angucyclines, likely as part of a hydrogen sulfide‐mediated detoxification process.